Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pone.0164202
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Human Fetal Mesenchymal Stem Cells with “Degenerating” Cerebellar Neurons in Spinocerebellar Ataxia Type 1 Model Mice

Abstract: Mesenchymal stem cells (MSCs) migrate to damaged tissues, where they participate in tissue repair. Human fetal MSCs (hfMSCs), compared with adult MSCs, have higher proliferation rates, a greater differentiation capacity and longer telomeres with reduced senescence. Therefore, transplantation of quality controlled hfMSCs is a promising therapeutic intervention. Previous studies have shown that intravenous or intracortical injections of MSCs result in the emergence of binucleated cerebellar Purkinje cells (PCs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 60 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…Surprisingly, the HNA antibody seems to stain cells in the Purkinje layer for all of the timepoints analyzed ( Figure S8C,E–H ). In fact, previous studies have already reported the fusion of hMSCs with the Purkinje cell layer when injected in murine models of SCA1 [ 63 ] and EAE [ 64 ], suggesting migration of hMSCs to mediate neuroprotection or rescue of highly differentiated sites. Nevertheless, and in spite of these observations, according to our behavioral analysis, hMSCs injected into the cerebellum of SCA3/MJD mice do not cause an amelioration of disease symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the HNA antibody seems to stain cells in the Purkinje layer for all of the timepoints analyzed ( Figure S8C,E–H ). In fact, previous studies have already reported the fusion of hMSCs with the Purkinje cell layer when injected in murine models of SCA1 [ 63 ] and EAE [ 64 ], suggesting migration of hMSCs to mediate neuroprotection or rescue of highly differentiated sites. Nevertheless, and in spite of these observations, according to our behavioral analysis, hMSCs injected into the cerebellum of SCA3/MJD mice do not cause an amelioration of disease symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of targeting either ATXN1 or other molecules involved in disease pathology, another therapeutic strategy aims to replace the cells that undergo neurodegeneration in SCA1 using stem cell replacement [119]. Several stem cell types can be used for replacement therapies, including pluripotent stem cells (PSCs) and multipotent stem cells, such as neural progenitor cells (NPCs) and mesenchymal stem cells (MSCs) (Table 4, [21,[119][120][121][122][123][124][125]). in the symptomatic mice [124] MSCs are multipotent and reside in several tissues but mainly in the bone marrow and fat, where they support hematopoiesis and produce cells of the mesodermal lineage.…”
Section: Stem Cell Replacement Therapiesmentioning
confidence: 99%
“…Cell fusion was also described to occur by some authors. Of note, this mechanism was described in a SCA1 mouse model, where Purkinje cells (PCs) of the host animals fused with MSC (Huda et al, 2016 ). However, this mechanism is rare in the literature and does not appear to account significantly for MSC’s overall outcomes.…”
Section: Mesenchymal Stromal Cells (Msc): Promising Tools For the Trementioning
confidence: 99%